The Role of Positive Discipline in The Digital Era: Fostering Inclusive Learning Environments - Tias Pramono; Achmad Ardiansyah; Mepa Kurniasih; Firdaus Putra; Dewiana Novitasari; Masduki Asbari; Zulfikar Muhammad; Hatoli Waruwu (Yayasan Aya Sophia Indonesia, 2024)
The half-day seminar on implementing positive discipline in schools aimed to provide high school principals and teachers with an in-depth understanding of the concepts, principles and implementation strategies of positive discipline. Through material presentation, discussion and experience exchange, participants were given insights into the importance of positive discipline in creating an inclusive learning environment and supporting students' holistic growth. Principals and teachers were empowered to become agents of change in implementing positive discipline practices in their schools, focusing on building positive relationships between students and educators, fostering students' social-emotional skills, and establishing a supportive school culture. As a result, participants expressed enthusiasm and desire to engage in follow-up seminars to enhance their understanding and skills in implementing positive discipline, and to continuously improve the learning environment in their schools.